2016
DOI: 10.1542/peds.2015-3684
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation and Late-Onset Sepsis in Preterm Infants: A Meta-analysis

Abstract: CONTEXT: Late-onset sepsis (LOS) is a major cause of mortality and morbidity in preterm infants. Despite various preventive measures, its incidence continues to remain high, hence the urgent need for additional approaches. One such potential strategy is supplementation with probiotics. The updated Cochrane Review (2014) did not find benefits of probiotics in reducing the risk of LOS in preterm infants (19 studies, N = 5338). Currently there are >30 randomized controlled trials (RCTs) of probiotics in preterm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 82 publications
6
134
4
5
Order By: Relevance
“…This phenomenon might lead to the development of strategies aimed at early manipulation of the microbiota to prevent LOS development, for example by administration of probiotics instead of antibiotic prophylaxis, reducing the risk for colonization with multi-resistant pathogens [21]. It has been demonstrated that probiotic supplementation significantly reduced the risk of LOS in preterm infants ( n = 9,416) [22]. However, additional studies are needed to evaluate the optimal dosage, duration, and identification of the best suitable bacterial strains for supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might lead to the development of strategies aimed at early manipulation of the microbiota to prevent LOS development, for example by administration of probiotics instead of antibiotic prophylaxis, reducing the risk for colonization with multi-resistant pathogens [21]. It has been demonstrated that probiotic supplementation significantly reduced the risk of LOS in preterm infants ( n = 9,416) [22]. However, additional studies are needed to evaluate the optimal dosage, duration, and identification of the best suitable bacterial strains for supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [46] proposed that probiotics might prevent bloodstream infections in low birthweight infants, but no effect was seen in children weighing <1000 g at birth. Rao et al also concluded that probiotics had a preventive effect [47] and likewise found that infants in a subgroup analysis (those born at <28 weeks' gestation and/or weighing <1000 g at birth) did not benefit from this intervention. Late-onset neonatal bloodstream infections were an outcome in the large probiotic study recently reported by Costeloe et al [48].…”
Section: Probiotics To Prevent Late-onset Neonatal Bloodstream Infectmentioning
confidence: 98%
“…Probiotic administration to preterm neonates may reduce rates of necrotizing enterocolitis 27 and nosocomial infection, 28 yet only 30% of Canadian neonates receive probiotics. 16 We will attempt to link receipt of probiotics during the neonatal intensive care unit stay as well as type, form (powder v. liquid), duration and timing of probiotic use with neonatal and neurodevelopmental outcomes.…”
Section: Probiotic Administrationmentioning
confidence: 99%